Christ in all Scripture: An Old Testament Perspective - Davidson, Richard M. (Kerygma, 2021)
Recent studies are challenging the hypothesis that NT writers mis-interpreted earlier Biblical writings, taking them out of context, and using interpretational techniques which are today considered “eisegesis”. However, biblical research is now confirming that the NT writers used the OT contextually, in continuity with the meaning found in the OT passages. It is the thesis of this article that the later Bible writers were exegetes in their biblical hermeneutics, remaining true to the Messianic meaning of those earlier biblical passages seen in their original context. I organize my discussion of “Christ in all Scripture” following Hasel’s synthesis of approaches, and under each of them I provide examples of how this approach has been utilized by Jesus and NT writers to see Christ in all OT Scripture. In light of the indicators of Christ in the Old Testament, Jesus’ sweeping claim in Luke 24 needs to be taken seriously.